Analysis Of Shopee Paylater User Features On Customer Satisfaction At Dehasen University” - Bella Augusta Aryati; Iswidana Utama Putra; M Rahman Febliansa (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the effect of Shopee PayLater features on customer satisfaction among students of the Faculty of Economics and Business, Dehasen University Bengkulu. The background of this research is based on the rapid development of digital technology that has brought significant changes to people’s transaction behavior. The emergence of financial technology (fintech) services provides consumers with practical, fast, and secure payment methods. One of the rapidly growing fintech innovations is the Buy Now Pay Later (BNPL) service, which allows users to purchase products first and pay later while supporting the improvement of digital financial literacy in higher education environments. This research employs a quantitative method with an associative approach. The population consists of active students of the Faculty of Economics and Business, Dehasen University Bengkulu, who use Shopee PayLater. A total of 91 respondents were selected using purposive sampling and the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using SPSS software. The data analysis included validity and reliability tests, multiple linear regression analysis, F-test, t-test, and the coefficient of determination (R²) to examine the effect of Shopee PayLater usage on customer satisfaction. The results show that the variables of ease of use, transaction security, and transaction comfort have a positive and significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination (R²) value of 0.817 indicates that 81.7% of the variation in customer satisfaction is explained by these three variables, while the remaining 18.3% is influenced by other factors outside this study. These findings suggest that the higher the level of ease, security, and comfort in using Shopee PayLater, the higher the satisfaction level among students of the Faculty of Economics and Business, Dehasen University Bengkulu toward the service.